Managing security issues and the hidden dangers of wearable technologies - Marrington, Andrew, 1982-; Kerr, Don, 1952-; Gammack, John, 1960- (Information Science Reference, 2017)
"This book examines the positive and negative ramifications of emerging wearable devices and their potential threats to individuals, as well as organizations, highlighting socio-ethical issues, policy implementation, and appropriate usage"- Resumé vydavatel
Keywords: technika a společnost; informační bezpečnost; riziko; information security; risk; technology and society; nositelné technologie; kolektivní monografie; elektronické knihy; collective monographs; electronic books